Spine Myeloid Sarcoma: A Case Series with Review of Literature - Shah, Kajal; Panchal, Harsha; Patel, Apurva (South Asian Journal of Cancer, 2021)
Myeloid sarcoma (MS) is a malignant extramedullary tumor consisting of immature cells of myeloid origin. It may precede, present concurrently or follow acute myeloid leukemia (AML) in de novo case or may also be present and might be the only manifestation of recurrent AML, myelodysplastic syndrome, or chronic myeloid leukemia. It frequently involves skin, orbit, bone, periosteum, lymph nodes, and gastrointestinal tract, soft tissue, central nervous system, and testis. Because of its different localization and symptoms, and the lack of diagnostic algorithm, MS is a real diagnostic challenge particularly in patients without initial bone marrow involvement. The correct diagnosis of MS is important for optimum therapy, which is often delayed because of a high misdiagnosis rate. We reported three cases of MS derived from spine presented with back pain, paraplegia, paraparesis, respectively, and reviewed the relevant literature.
Keywords: Keywords; acute myeloid leukemia; chronic myeloid leukemia; granulocytic sarcoma; myelodysplastic syndrome; myeloid sarcoma